112-2x=6x+16

Simple and best practice solution for 112-2x=6x+16 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 112-2x=6x+16 equation:


Simplifying
112 + -2x = 6x + 16

Reorder the terms:
112 + -2x = 16 + 6x

Solving
112 + -2x = 16 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
112 + -2x + -6x = 16 + 6x + -6x

Combine like terms: -2x + -6x = -8x
112 + -8x = 16 + 6x + -6x

Combine like terms: 6x + -6x = 0
112 + -8x = 16 + 0
112 + -8x = 16

Add '-112' to each side of the equation.
112 + -112 + -8x = 16 + -112

Combine like terms: 112 + -112 = 0
0 + -8x = 16 + -112
-8x = 16 + -112

Combine like terms: 16 + -112 = -96
-8x = -96

Divide each side by '-8'.
x = 12

Simplifying
x = 12

See similar equations:

| 2f+g=13 | | a+4b=18 | | 24-t=18 | | h-14=23 | | 20-1.45=1.15 | | 3(2+x)=10+x | | 4x=3+3x | | x-2-8=3 | | 6v=24 | | t+26=41 | | (x^5+y^2)(x^5-Y^2)= | | 0=8+2y | | 2(123*34)= | | 110=80+2xwidth | | 4x^2-3x+16=0 | | -4.3-.1x=-6.1 | | (5a-1)(6a-3)= | | -15+5x=11+3x | | 0=2x+10 | | -5+5x=11+3x | | 0=x+5 | | 0=x-1 | | -2+3x=14+5x | | 8-1=63 | | 0.12(6)+0.02x=0.04(12+x) | | -9v+9=10(8v-8) | | 0.12y+0.09(y+4000)=1410 | | -2(x+16)+3(2x-5)=3(x-4)+10 | | 5x+26=2x+98 | | 2(4x-1)+3(3-2x)=0 | | 7+n=2n | | 4x+17=8x+10 |

Equations solver categories